2007
DOI: 10.1111/j.1365-2044.2006.04944_8.x
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of the use of ultrasound locating devices for placing central venous catheters

Abstract: modifications, the system could prove to be the first practical design step to preventing accidental crossconnection of neuraxial and intravenous lines, thereby improving patient safety. There is a good correlation between the calculated effect site concentration and the depth of anaesthesia. Propofol is known to depress the cardiovascular system but the relationship between the effect site concentration and cardiovascular depression has not been extensively studied. A previous study by Kazama et al. showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Other reasons advanced for the reluctance to take up US range from the relative paucity of studies involving anaesthetists to the lack of representation on the NICE committee of anaesthetic consultants. 22 The argument that US machines are not available no longer seems to hold water after the publication of a survey by Harris and colleagues 23 that showed 86% of departments had a US locating device.…”
Section: Discussionmentioning
confidence: 99%
“…Other reasons advanced for the reluctance to take up US range from the relative paucity of studies involving anaesthetists to the lack of representation on the NICE committee of anaesthetic consultants. 22 The argument that US machines are not available no longer seems to hold water after the publication of a survey by Harris and colleagues 23 that showed 86% of departments had a US locating device.…”
Section: Discussionmentioning
confidence: 99%
“…Although our survey did not determine a reason for this, a survey conducted by NICE, in 2005, found that of 250 consultant anaesthetists questioned, 67% had received poor or no training in the use of 2D ultrasound devices [7]. However, training in use of 2D ultrasound devices appears to be increasing and comes from a variety of sources ranging from the manufacturers of the devices to informal teaching from experienced colleagues [9]. Overall, 75% of respondents stated they would use ultrasound as a first, second or third choice leaving us with the assumption the majority are comfortable with the technique.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendation for the use of ultrasound in the insertion of central lines in the NICE guidelines of 2002 [3] has resulted in an increase in the availability of portable ultrasound machines in the theatre environment. A study in 2007 found that 86% of departments had access to ultrasound [4].…”
Section: Introductionmentioning
confidence: 99%